Pengaruh Intervensi Terapi Hypnobreastfeeding Terhadap Tingkat Kecemasan pada Ibu Primipara Pasca Operasi Sectio Caesarea - Leony Gita Amiyarti; Nur Azizah Indriastuti; Eny Hernani (Jurnal Medika Nusantara, 2024)
Background: Sectio Caesarea (SC) is currently an alternative method of delivery for mothers. Delivery by sectio caesarea method in primipara mothers can cause anxiety problems. One way to reduce anxiety is with hypnobreastfeeding technique. Objective: Apply hypnobreastfeeding therapy and determine the effect of hypnobreastfeeding therapy on the anxiety level of primiparous mothers with post sectio caesarea. Methods: The method used in this study is a case study conducted on patients who are primiparous mothers after cesarean section with anxiety using hypnobreastfeeding therapy. This therapy was conducted for 2 days from May 10, 2024 - May 11, 2024 at PKU Muhammadiyah Gamping Hospital. Results: From the case study conducted for 2 interventions, a decrease in anxiety was obtained as evidenced by the results of the HARS score showing anxiety decreased to 18 (mild anxiety) from the previous 22 (moderate anxiety). Conclusion: Based on the results of the analysis and discussion carried out on the case study report entitled “The Effect of Hypnobreastfeeding Therapy Intervention on Anxiety Levels in Primiparous Mothers After Sectio Caesarea Surgery” it can be concluded that hypnobreastfeeding therapy is effective for reducing anxiety in postoperative sectio caesarea mothers.